Heterozygous Deletion of the SHOX Gene Enhancer in two Females With Clinical Heterogeneity Associating With Skewed XCI and Escaping XCI - Sun, Yixi; Luo, Yuqin; Qian, Yeqing; Chen, Min; Wang, Liya; Li, Hongge; Zou, Yu; Dong, Minyue (Frontiers in Genetics, 2019)
Skewed X-chromosome inactivation (XCI) plays an important role in the phenotypic heterogeneity of X-linked disorders. However, the role of skewed XCI in XCI–escaping gene SHOX regulation is unclear. Here, we focused on a heterozygous deletion of SHOX gene enhancer with clinical heterogeneity. Using SNP array, we detected that the female proband with Leri-Weill dyschondrosteosis (LWD) carried an 857 kb deletion on Xp22.3 (encompassing SHOX enhancer) and a 5,707 kb large-fragment deletion on Xq25q26. XCI analysis revealed that the X-chromosome with the Xq25q26 large-fragment deletion was completely inactivated, which forced the complete activation of the other X-chromosome carrying SHOX enhancer deletion. While the Xp22.3 deletion locates on the escaping XCI region, under the combined action of skewed XCI and escaping XCI, transcription of SHOX gene was mainly from the activated X-chromosome with SHOX enhancer defect, involving in the formation of LWD phenotype. Interestingly, this SHOX enhancer deletion was inherited from her healthy mother, who also demonstrated completely skewed XCI. However, the X-chromosome with SHOX enhancer deletion was inactivated, and the normal X-chromosome was activated. Combing with escaping XCI, her phenotype was almost normal. In summary, this study was a rare report of SHOX gene enhancer deletion in a family with clinical heterogeneity due to skewed inactivation of different X-chromosomes, which can help in the genetic counseling and prenatal diagnosis of disorders in females with SHOX defect.